Validation of calipso space-borne-derived attenuated backscatter coefficient profiles using a ground-based lidar in Athens, Greece - Mamouri, Rodanthi-Elisavet; Amiridis, Vassilis; Papayannis, Alexandros D.; Giannakaki, Elina; Tsaknakis, Georgios; Balis, Dimitris S. (My University, 2009)
We present initial aerosol validation results of the space-borne lidar CALIOP -onboard the CALIPSO satellite- Level 1 attenuated backscatter coefficient profiles, using coincident observations performed with a ground-based lidar in Athens, Greece (37.9° N, 23.6° E). A multi-wavelength ground-based backscatter/Raman lidar system is operating since 2000 at the National Technical University of Athens (NTUA) in the framework of the European Aerosol Research LIdar NETwork (EARLINET), the first lidar network for tropospheric aerosol studies on a continental scale. Since July 2006, a total of 40 coincidental aerosol ground-based lidar measurements were performed over Athens during CALIPSO overpasses. The ground-based measurements were performed each time CALIPSO overpasses the station location within a maximum distance of 100 km. The duration of the ground-based lidar measurements was approximately two hours, centred on the satellite overpass time. From the analysis of the ground-based/satellite correlative lidar measurements, a mean bias of the order of 22% for daytime measurements and of 8% for nighttime measurements with respect to the CALIPSO profiles was found for altitudes between 3 and 10 km. The mean bias becomes much larger for altitudes lower that 3 km (of the order of 60%) which is attributed to the increase of aerosol horizontal inhomogeneity within the Planetary Boundary Layer, resulting to the observation of possibly different air masses by the two instruments. In cases of aerosol layers underlying Cirrus clouds, comparison results for aerosol tropospheric profiles become worse. This is attributed to the significant multiple scattering effects in Cirrus clouds experienced by CALIPSO which result in an attenuation which is less than that measured by the ground-based lidar.
Keywords: Aerosols; Optical radar; Backscattering; Troposphere